1992
DOI: 10.1016/0304-3959(92)90143-y
|View full text |Cite
|
Sign up to set email alerts
|

Pain complaint and the weather: weather sensitivity and symptom complaints in chronic pain patients

Abstract: Chronic pain patients frequently report that weather conditions affect their pain; however, no standardized measures of weather sensitivity have been developed. We describe the development and use of the Weather and Pain Questionnaire (WPQ) which assess patient sensitivity to meteorologic variables defined by the National Weather Service (e.g., temperature, precipitation). Seventy chronic pain patients (59% females) with an average age of 43 years completed the WPQ. The instrument was revised using factor anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 19 publications
1
49
0
2
Order By: Relevance
“…Another possibility is that patients may tend to attribute their pain to the weather because of its prominence. 31 Alternatively, there may also be a tendency to a confirmatory bias stemming from anecdotal beliefs about pain and weather. 10 31 Weather sensitivity has been associated with the personality characteristics of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that patients may tend to attribute their pain to the weather because of its prominence. 31 Alternatively, there may also be a tendency to a confirmatory bias stemming from anecdotal beliefs about pain and weather. 10 31 Weather sensitivity has been associated with the personality characteristics of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of studies concerning WS related to conditions such as chronic pain (Jamison et al 1995;Shutty et al 1992), rheumatoid arthritis (Gorin et al 1999;Drane et al 1997;Hagglund et al 1994) or psychological impairments (Vadzyuk and Mikula 1997;Faust and Hole 1972). Some of these studies have demonstrated a relationship between weather conditions and the occurrence of industrial and car accidents, excluding trivial reasons such as icy ground or storms (Rauschhofer et al 1981;Jendritzky et al 1978).…”
Section: Introductionmentioning
confidence: 98%
“…In the nineteenth century, several authors suggested that variations in barometric pressure, in particular, were partially responsible for variations in the intensity of arthritis pain (2)(3)(4). To the current day, such beliefs are common among patients, physicians, and interested observers throughout the world (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Furthermore, these beliefs have led to recommendations that patients move to milder climates or spend time in a climate-controlled chamber to lessen joint pain (15)(16)(17).…”
mentioning
confidence: 99%